Effects of Pumping Scheme and Double-Propagation on the Performance of ASE Source using Dual-Stage Bismuth-Based Erbium-Doped Fiber - Ahmad, Harith; Cheng, Xiau San; Tamjis, Mohamad Rom; Harun, Sulaiman Wadi (Taylor & Francis, 2010)
In this paper, a new configuration of the wide-band amplified spontaneous emission (ASE) source is proposed using dual-stage scheme with a broadband fiber Bragg grating. The ASE source utilizes a Bismuth-based erbium-doped fiber (Bi-EDF) as a gain medium with either forward or backward pumping scheme. A wide-band and flat ASE output is achieved using a forward pumping scheme with the power ripples of less than 4.9 dB and 3 dB bandwidth of 90.5 nm. The ASE spectrum obtained covers the whole C-, L- and extended L-band regions from 1520 to 1620 nm. However, the backward pumping scheme provides a better pumping efficiency as compared to the forward pumping. The total ASE power reaches up to 26.6 mW at maximum pump power of 320 mW with a pumping efficiency of 8%.